2012
DOI: 10.1270/jsbbs.62.3
|View full text |Cite
|
Sign up to set email alerts
|

Accurate evaluation and verification of varietal ranking for flooding tolerance at the seedling stage in barley (<i>Hordeum vulgare</i> L.)

Abstract: Soil flooding or waterlogging is a major abiotic stress in upland crops. In barley, there have been several reported studies of selection for flooding-tolerant genotypes, but it is difficult to obtain varietal rankings that are consistent among researchers. Our objectives were to establish experimental conditions that could be applied by other research groups and to verify the varietal ranking conducted in an earlier study. We conducted greenhouse experiments on 14 barley varieties. At the 2.5-leaf stage, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Quantitative trait loci (QTLs) associated with CAF in Z. nicaraguensis have been examined using populations of maize inbred line Mi29 crossed with Z. nicaraguensis (Mano and Omori, 2008, 2009), maize inbred line B64 crossed with Z. nicaraguensis (Mano et al , 2007), and S 1 and S 2 segregants of Z. nicaraguensis (Mano et al , 2012). So far, seven QTLs have been identified (Mano et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci (QTLs) associated with CAF in Z. nicaraguensis have been examined using populations of maize inbred line Mi29 crossed with Z. nicaraguensis (Mano and Omori, 2008, 2009), maize inbred line B64 crossed with Z. nicaraguensis (Mano et al , 2007), and S 1 and S 2 segregants of Z. nicaraguensis (Mano et al , 2012). So far, seven QTLs have been identified (Mano et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that selecting genotypes with least reduction in photosynthetic rate or total chlorophyll content may facilitate identification of tolerant types (Pang et al, 2004). Quantitative trait loci (QTL) associated with tolerance to waterlogging in barley have been identified using combinations of leaf chlorosis, plant biomass production and plant death (Li et al, 2008(Li et al, , 2013Mano and Takeda, 2012;Zhou, 2011;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth is also inhibited by waterlogging, and dry matter accumulation is reduced (Osman et al, 2013;Zou et al, 2014a). Certainly, the yield of important crops including maize (Qiu et al, 2007), wheat (Setter et al, 2009;Yu and Chen, 2013), rapeseed (Zou et al, 2014a) and barley (Mano and Takeda, 2012) decrease drastically due to waterlogging.…”
Section: Introductionmentioning
confidence: 99%